Teacher Professional Development and Self-Development - Bulajeva, Tatjana (Acta Paedagogica Vilnensia, 2000)
This article gives the overview of the latest developments in the field of teacher development. It discusses the traditional ways of teacher development and new perspective of self-development that lead to transformative learning. Transformative learning is of great importance because it leads to the transformation of teachers’ beliefs, values, assumptions and consequently leads to the changes in teacher behaviour. Special attention is given to self-direction, adopting Candy's framework of four distinct but interrelated phenomena. Self-direction is seen to have the dimensions of personal autonomy, self-management, and learner control and auto-didactics. Each dimension is both a goal and a process.
Keywords: Teacher professional development; self-development; autonomy; self-government.